Special exercises in the style of CROSS FIT and their effect on developing the skill of defense against shooting by jumping from within the three-point arc of basketball for the youth category - Alaa Mohsen Al-Taee, Hussain; Ahmed Neamah, Shihab (International Journal of Psychosocial Rehabilitation, 2020)
The selection of appropriate training methods is one of the factors that are given great importance in modern sports training, and among these training methods are CrossFit exercises, which is a method that increases the individual’s physical fitness and increases the strength of the body’s muscles in addition to determining the shape of the body’s muscles and improving their work from In all respects, in order to keep pace with the development witnessed by the game of basketball and the expansion of its base and its spread in most countries of the world, including Iraq, and because this game contains awonderful mix of skills, this game requires the skill of carrying out offensive operations and returning with the same efficiency to defense, and there is no doubt that the moves inside the stadium Basketball is continuous from all players to achieve a good attack, as the rapid change of playing positions requires the high physical ability to move, move and respond quickly. Here lies the importance of research on the effect of CrossFit exercises in the defensive skills under study that contribute to the performance of these skills, as they are included Exercises that help develop them while playing.